2014
DOI: 10.1038/ncomms6456
|View full text |Cite
|
Sign up to set email alerts
|

The immunoglobulin tail tyrosine motif upgrades memory-type BCRs by incorporating a Grb2-Btk signalling module

Abstract: The vigorous response of IgG-switched memory B cells to recurring pathogens involves enhanced signalling from their B-cell antigen receptors (BCRs). However, the molecular signal amplification mechanisms of memory-type BCRs remained unclear. Here, we identify the immunoglobulin tail tyrosine (ITT) motif in the cytoplasmic segments of membrane-bound IgGs (mIgGs) as the principle signal amplification device of memory-type BCRs in higher vertebrates and decipher its signalling microanatomy. We show that different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(104 citation statements)
references
References 43 publications
7
94
0
Order By: Relevance
“…The difference between the recall abilities of wild type and ITT-mutant IgG1 memory B cells was as striking as in the presence of T cells34 . The same result was obtained when Grb2-negative and Grb2-positive IgG memory B cells were compared in the same assay33 , showing that not only the ITT itself but also its downstream signaling pathway is required to lower the activation threshold of the IgG memory B cell compartment and thereby favor IgG-production in secondary antibody responses under competitive conditions. Given the strict conservation of ITT motifs in all surface IgG isotypes, the data show that ITT-controlled signaling is essential for proper reactivation of IgG-switched memory B cells.The discovery of an IgG-BCR-intrinsic signal amplification mechanism together with improved affinity for antigen provides molecular explanations as to why IgG-positive memory B cells are responsive in the presence of circulating antibodies while IgM-positive memory B cells are not.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…The difference between the recall abilities of wild type and ITT-mutant IgG1 memory B cells was as striking as in the presence of T cells34 . The same result was obtained when Grb2-negative and Grb2-positive IgG memory B cells were compared in the same assay33 , showing that not only the ITT itself but also its downstream signaling pathway is required to lower the activation threshold of the IgG memory B cell compartment and thereby favor IgG-production in secondary antibody responses under competitive conditions. Given the strict conservation of ITT motifs in all surface IgG isotypes, the data show that ITT-controlled signaling is essential for proper reactivation of IgG-switched memory B cells.The discovery of an IgG-BCR-intrinsic signal amplification mechanism together with improved affinity for antigen provides molecular explanations as to why IgG-positive memory B cells are responsive in the presence of circulating antibodies while IgM-positive memory B cells are not.…”
supporting
confidence: 74%
“…A first clue to memory-type BCR-specific signaling was provided by a genetic mouse model with targeted deletion of the highly conserved cytoplasmic IgG1 segment consisting of 28 amino acids that are absent in surface which is the immediate upstream activator of PLC-ɣ2 33 (Figure 1). Interestingly, when the ITT was engineered into the IgM-BCR, the resulting chimera signaled like a wild type IgG-BCR 31 .…”
Section: Biochemical and Gene Targeting Experiments Uncover Molecularmentioning
confidence: 99%
“…Their studies provided the first line of evidence for a direct interaction of the cytoplasmic tail of mIgG with a well characterized BCR signaling molecule, Grb2, which could be recruited to the pITT-Tyr through its SH2 domain after IgG-BCR and antigen recognition, leading to the enhancement of calcium responses and B cell proliferation. Their very recent studies demonstrated that Grb2 in turn recruited Bruton's tyrosine kinase (Btk) via a constitutive manner that is mediated by the N-terminal SH3 domain of Grb2 (Engels et al, 2014). The constitutive incorporation of Grb2 and Btk module into the membrane proximal IgG-BCR signalosome lowers the threshold for activation of PLCg2 by Btk and amplifies the BCR-induced calcium mobilization, which subsequently improves IgGþ B cell proliferation (Fig.…”
Section: The Cytoplasmic Tail Of Migg Enhances the Transmembrane Signmentioning
confidence: 97%
“…The recruitment of Grb2 into the mIgG-BCR signalosome brings along Btk via a constitutive interaction that is mediated by the N-terminal SH3 domain of Grb2 and proline-rich region of Btk. The participation of Grb2/Btk in the BCR signalosome stabilizes the Ca 2+ signal scaffold consisting of Btk, BLNK, and PLC-γ2 during the BCR engagement and thereby might lower the threshold for activation of PLC-γ2 by Btk (Engels et al 2014). …”
Section: Soce Regulatormentioning
confidence: 98%
“…Ca 2+ signaling was enhanced upon cross-linking of mIgG-type BCR compared to mIgM-type BCR (Waisman et al 2007), which is dependent on the tyrosine phosphorylation in the cytoplasmic tail segment (Engels et al 2009;Horikawa et al 2007). Grb2 does not interact with mIgM/Igα/Igβ complex, but can bind with the immunoglobulin tail tyrosine (ITT) motif in the cytoplasmic tail segment of the IgG heavy chain when it is phosphorylated by Syk (Engels et al 2014). The recruitment of Grb2 into the mIgG-BCR signalosome brings along Btk via a constitutive interaction that is mediated by the N-terminal SH3 domain of Grb2 and proline-rich region of Btk.…”
Section: Soce Regulatormentioning
confidence: 98%